Implementation of a comprehensive feeding, good animal husbandry practice and flock health programme for AFF Aqil Aqilah ayam kampung farm - Idris, Lokman Hakim; Abu Bakar @ Zakaria, Md Zuki; Kassim, Azhar; Mohd Apandi, Mohamad Aqmal; Mohd Esa, Shakinah (Knowledge Transfer Programme, 2017)
There is a high challenge to increase the production of Ayam Kampung in Malaysia especially in semi-commercial farms. Basically, Ayam Kampung has slow growth rates, high prevalence of disease, high Feed Conversion Ratio (FCR) resulting in high production cost. A holistic approach on implementing Good Animal Husbandry Practice (GAHP), feeds modification, flock health program including biosecurity and the usage of effective microbes can tremendously improve the overall farm performance. At AFF Aqil Aqilah farm, a low production performance of Ayam Kampung with respect to the high production cost, low uniformities, feed utilization and disease resistance, high working hours and under farm capacity production were observed. These were associated to improper rearing management specifically on farm design, feeding and flock health management. Therefore, there is a great need to improve the rearing management system by implementing GAHP, economical feed formulation, flock health program, biosecurity and introducing effective microbes for the Ayam Kampung production. This program shows high impact by reducing farm production cost, increase the farm production, income and improved the farmers and graduate intern skills.